RAVEN: Enhancing Test Request Reliability through Real-Time Verification in High-Complexity Systems - Lima, Rayfran Rocha; Silva, Rodrigo Carvalho (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2025: Anais do X Simpósio Brasileiro de Testes de Software Sistemático e AutomatizadoDO - 10.5753/sast.2025.13677, 2025)
In embedded software projects for mobile devices, test requests are critical to ensuring product quality, yet complex dependencies on binaries, version control, and country-specific configurations often cause submission errors. These errors lead to inefficiencies and delays in testing pipelines. This paper reports on the development and evaluation of RAVEN (Request Assessment and Verification Engine), a real-time verification system built through an Action Research approach. RAVEN integrates data from JIRA, version control systems, and binary baselines to automatically verify over 30 criteria as users fill out request forms. Deployed in an industrial environment, RAVEN improved process efficiency—reducing approval lead time by 58%, halving submission iterations—and enhanced reliability, lowering the rejection rate of a key request type by 17 percentage points. It also improved the clarity of verification feedback and fostered greater requester accountability. A TAM-based questionnaire confirmed high user-perceived usefulness and ease of use. While some verification gaps remain, RAVEN demonstrated the value of proactive, educational verification. Future work includes extending its scope, integrating ML-based recommendations, and replicating the approach in other contexts.